Penyuluhan Hipertensi Pada Lansia Di Desa Jelok, Cepogo, Boyolali - Sukmaningsih, Wahyu Ratri; Suparti, Sri; Elisabrina, Diyah (Politeknik Indonusa Surakarta, 2024)
Hypertension is one of the main health problems in the elderly that is often not detected early but has a high risk of causing complications such as heart disease, stroke, and kidney failure. Health education is one of the strategic efforts to increase awareness and knowledge of the elderly regarding the prevention and management of hypertension. This activity was carried out in Jelok Village, Cepogo, Boyolali, with the aim of providing education about hypertension, prevention, and healthy lifestyles to the elderly. The activity methods include lectures, interactive discussions, and demonstrations of blood pressure measurements. The material presented includes the definition of hypertension, risk factors, symptoms, impacts, and preventive measures through a healthy lifestyle. Participants are also provided with leaflets as an independent guide. Evaluation was carried out through pretests and posttests to measure changes in participants' understanding before and after the education. The results of the activity showed an increase in knowledge with an average posttest score increasing by 89% compared to the pretest. This activity proves that the community-based education method is effective in increasing health awareness in the elderly. It is hoped that this activity can be a sustainable model for managing elderly health, both in Jelok Village and in other areas. Keywords: Hypertension, Elderly, Knowledge, Education